2004
DOI: 10.1177/135676670401000204
|View full text |Cite
|
Sign up to set email alerts
|

Tourist purchase decision involvement and information preferences

Abstract: This study examines the relationships between tourists’ purchase decision involvement and their information search behaviours. The behaviours include their information preferences as measured by perceived value of different types of information contents, and their use of the internet as an information channel. The relationships are presented in a proposed conceptual framework of the tourist information search process, and tested through two hypotheses using a survey sample. The findings reveal that tourist inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
106
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(114 citation statements)
references
References 43 publications
4
106
0
4
Order By: Relevance
“…An inquiry into the information search behavior of a potential tourist involves determining what to search (information contents) and where to search (information channels) [68]. Moutinho [25] defined information search as an expressed need to consult various sources prior to making a purchase decision.…”
Section: Tourist Information Searchmentioning
confidence: 99%
“…An inquiry into the information search behavior of a potential tourist involves determining what to search (information contents) and where to search (information channels) [68]. Moutinho [25] defined information search as an expressed need to consult various sources prior to making a purchase decision.…”
Section: Tourist Information Searchmentioning
confidence: 99%
“…A variety of studies link source of information to influencing and determining consumer behavior (Cai, Feng, & Breiter, 2004;Murphy, Mascardo, & Benckendorff, 2007). This is integral to determining where and how customers acquire information, which thereby assists managers in making informed marketing decisions.…”
Section: Source Of Informationmentioning
confidence: 99%
“…The second approach focuses on the economic impact that the customer perceives (how much the trip will cost and limiting the risks associated with the trip), the third approach is the physical act of searching for information, and the fourth uses information search behavior as a way to segment customers. Cai, Feng, and Breiter (2004) also discuss information searches in relation to purchase level involvement and found that the content of the information depended on the level of involvement in the purchase.…”
Section: Source Of Informationmentioning
confidence: 99%
“…Research published in the Journal of Vacation Marketing has established that the level of involvement with the purchase decision influences the type of information travellers seek (Cai et al 2004). Clearly, an overseas wedding is a high involvement decision entailing risk and as such lends itself well to technology and web marketing.…”
Section: Introductionmentioning
confidence: 99%
“…Within tourism management literature, the factors that affect tourists purchase involvement (Cai et al 2004) or more specifically, influence a couples' choice of honeymoon destination have been examined (Jang et al 2007;Kim and Agrusa, 2005). While these articles provide useful contributions to helping understand factors that influence international travel marketing experiences, they may not capture the complexity of a consumer's buying decision in the weddings abroad market.…”
Section: Introductionmentioning
confidence: 99%